Comparison of western diet-induced obesity and streptozotocin mouse models: insights into energy balance, somatosensory dysfunction, and cardiac autonomic neuropathy - Elshareif, Nadia; Gornick, Emily; Gavini, Chaitanya K.; Aubert, Gregory; Mansuy-Aubert, Virginie (Frontiers in Physiology, 2023)
Metabolic disorders such as obesity and type 2 diabetes (T2D) are increasingly prevalent worldwide, necessitating a deeper comprehension of their underlying mechanisms. However, translating findings from animal research to human patients remains challenging.This study aimed to investigate the long-term effects of Streptozotocin (STZ) on metabolic, cardiac, and somatosensory function in mice fed a Western diet (WD) of high fat, sucrose, and cholesterol with low doses of STZ administration compared to mice fed WD alone. In our research, we thoroughly characterized energy balance and glucose homeostasis, as well as allodynia and cardiac function, all of which have been previously shown to be altered by WD feeding. Notably, our findings revealed that the treatment of WD-fed mice with STZ exacerbated dysfunction in glucose homeostasis via reduced insulin secretion in addition to impaired peripheral insulin signaling. Furthermore, both WD and WD+STZ mice exhibited the same degree of cardiac autonomic neuropathy, such as reduced heart rate variability and decreased protein levels of cardiac autonomic markers. Furthermore, both groups developed the same symptoms of neuropathic pain, accompanied by elevated levels of Activating Transcription Factor (ATF3) in the dorsal root ganglia. These discoveries enhance our understanding of metabolic activity, insulin resistance, neuropathy, and cardiac dysfunction of diet-induced models of obesity and diabetes.The exacerbation of impaired insulin signaling pathways by STZ did not lead to or worsen cardiac and somatosensory dysfunction. Additionally, they offer valuable insights into suitable diet induced translational mouse models, thereby advancing the development of potential interventions for associated conditions.